In-situ neutron diffraction investigation on twinning/detwinning activities during tension-compression load reversal in a twinning induced plasticity steel. (June 2018) - Xie, Q.; Chen, Y.; Yang, P.; Zhao, Z.; Wang, Y.D.; An, K.
Abstract: The tension-compression type of load reversal produces an asymmetric cyclic tension-compression behavior and varied yielding stresses in the subsequent monotonic tension and compression in a twinning induced plasticity steel. The micromechanical behavior was elucidated via the evolutions of the stacking fault probability and the grain orientation density captured by in-situ neutron diffraction. The latter indicates more profound detwinning activities in a reversal from tension to compression than those from compression to tension and more twinning involves in monotonic tension than in compression. This is confirmed by the calculated twinning activities in monotonic tension and compression using the visco-plastic self-consistent model. Graphical abstract: Unlabelled Image